The Alliance for Freshwater Life: A global call to unite efforts for freshwater biodiversity science and conservation. Issue 4 (13th August 2018) - Darwall, William; Bremerich, Vanessa; De Wever, Aaike; Dell, Anthony I.; Freyhof, Jörg; Gessner, Mark O.; Grossart, Hans‐Peter; Harrison, Ian; Irvine, Ken; Jähnig, Sonja C.; Jeschke, Jonathan M.; Lee, Jessica J.; et al.
Abstract: Global pressures on freshwater ecosystems are high and rising. Viewed primarily as a resource for humans, current practices of water use have led to catastrophic declines in freshwater species and the degradation of freshwater ecosystems, including their genetic and functional diversity. Approximately three‐quarters of the world's inland wetlands have been lost, one‐third of the 28 000 freshwater species assessed for the International Union for Conservation of Nature (IUCN) Red List are threatened with extinction, and freshwater vertebrate populations are undergoing declines that are more rapid than those of terrestrial and marine species. This global loss continues unchecked, despite the importance of freshwater ecosystems as a source of clean water, food, livelihoods, recreation, and inspiration. The causes of these declines include hydrological alterations, habitat degradation and loss, overexploitation, invasive species, pollution, and the multiple impacts of climate change. Although there are policy initiatives that aim to protect freshwater life, these are rarely implemented with sufficient conviction and enforcement. Policies that focus on the development and management of fresh waters as a resource for people almost universally neglect the biodiversity that they contain. Here we introduce the Alliance for Freshwater Life, a global initiative, uniting specialists in research, data synthesis, conservation, education and outreach, and policymaking. This expert network aims to provide the critical mass required for the effective representation of freshwater biodiversity at policy meetings, to develop solutions balancing the needs of development and conservation, and to better convey the important role freshwater ecosystems play in human well‐being. Through this united effort we hope to reverse this tide of loss and decline in freshwater biodiversity. We introduce several short‐ and medium‐term actions as examples for making positive change, and invite individuals, organizations, authorities, and governments to join the Alliance for Freshwater Life .